Penggunaan Media Quizizz dalam Penguasaan Kosa Kata Bahasa Inggris bagi Kelompok Pemuda di Gereja Bethel Diaspora Karanganyar Jawa Tengah - Ch. Evy Tri Widyahening; Sumardiono Sumardiono (LPPM Universitas Flores, 2022)
English is the first foreign language that must be learned and mastered by everyone, especially students. Its role in the international world is also very important such as in the fields of politics, economy, socio-culture, education, and others. Not only students need to learn English but also the younger generation, especially the youth who are members of the D'Generation group, under the guidance of the Bethel Diaspora Church of Karanganyar, Central Java. Most of them are workers and because they are busy at work, they cannot use English actively or even do not master English. The main element that needs to be learned in English is vocabulary. By mastering English vocabulary, it is certain that learning English will be much easier and more enjoyable. In this case, the use of learning media is very necessary to optimize the process of mastering English vocabulary during this covid 19 pandemic. For this reason, in this training, Quizizz media is used which can be downloaded via the play store on their smartphones. The purpose of this training is to improve the English vocabulary of the youth who are members of the D'Generation group at Bethel Diaspora Church, Karanganyar, Central Java by using the Quizizz media. This training program is carried out for 2 months by online or using Google Meet in meetings. After completing the training program, the youth who participated felt more motivated and able to understand and master English vocabulary well through the fun Quizizz media.